Pemberdayaan Masyarakat Melalui Pelatihan Persiapan dan Pengemasan Area Kerja Massage dan Lulur Berbasis Service Excellent - Sofia Daniati; Irene Fiolina; Nina Shafana Abnajapa (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Services in the field of beauty, especially massage and scrub treatments, demand high standards of cleanliness, neatness, and comfort as part of the principle of service excellence. In order to improve the quality of service and professionalism of beauty practitioners, this training activity was held with a focus on the preparation and packaging of the work area. The main purpose of the training is to provide knowledge and skills to participants in arranging the workspace in a clean, neat, and according to industry standards, so as to be able to create a comfortable atmosphere and support customer satisfaction. The training methods used include direct delivery of material by the instructor as well as interactive question and answer sessions to deepen participants' understanding. The training materials include the basic principles of work area cleanliness, the arrangement of tools and materials, the packaging of the treatment room before and after service, and professional ethics in welcoming and serving customers. Participants are trained to pay attention to the visual and functional details of the work area, including lighting, scent, and the physical comfort of customers. The results of the training showed that participants had an increased understanding of the importance of packaging work areas as an integral part of service quality. In addition, participants showed enthusiasm in applying the principles they had learned into their daily work practices. This activity is considered a strategic step in empowering the workforce in the beauty sector, encouraging increased competitiveness and professionalism amid the increasingly competitive demands of the body care services industry. With this training, it is hoped that more consistent and quality service standards will be created, as well as a work culture that prioritizes customer comfort and professional integrity. Similar training needs to be developed on an ongoing basis to strengthen the capacity of beauty practitioners in the face of industry dynamics and evolving consumer expectations.